Peningkatan Pendidikan Berkualitas Dalam Mewujudkan Sustainable Development Goals (SDGs) - Muala, Asyharul; Nugraheni, Nursiwi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Quality education is currently the main focus of government programs that continue to be pursued. Efforts to achieve good educational standards are not solely the responsibility of the government, but involve contributions from the private sector, educational institutions and the general public. This research aims to illustrate the vitality of efforts to develop the quality of Indonesian education, a country facing challenges in terms of educational quality. The research method used is a qualitative literature study approach and a descriptive approach. The data collected comes from scientific literature such as journals and articles. The results of this research provide insight into efforts that can be made to improve the quality of education in Indonesia, and identify several factors that contribute to the low quality of education in this country. In achieving the goal of impactful learning in the classroom and improving the overall quality of education, the role of professional development for educators is very important.